(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The content of the article is as follows, important changes in the field of education, the application of new pedagogical technologies to science, the use of effective methods in the organization of the lesson process, the ability to know foreign languages is becoming one of the integral parts of professional education today. , these are mentioned in detail.